Assessment of histotripsy as a bone-sparing tumor ablation technique in ex vivo osteosarcoma tumor-affected limbs - Achari, Preeya F.; Vickers, Elliana; Ruger, Lauren; Vlaisavljevich, Eli; Tuohy, Joanne; Collins, Caitlyn J. (Frontiers in Veterinary Science, 2026)
BackgroundOsteosarcoma (OS) is an aggressive primary bone cancer that is highly resistant to conventional therapies. Histotripsy, a non-invasive and non-thermal focused ultrasound ablation technique, has recently been explored as a treatment for OS in a canine comparative anatomy model exhibiting heterogeneous tumor phenotypes. However, the biomechanical effects of histotripsy on OS tumor-bearing bone and adjacent grossly normal bone remain unknown. This study aimed to evaluate the impact of histotripsy on the mechanical properties of bone and to characterize tumor heterogeneity.MethodsEx vivo limbs from canine OS patients (n = 10) were used to collect tumor-affected and normal bone specimens. Histotripsy ablation was performed on both tissue types, with corresponding unablated tumor and normal controls. Mechanical testing, including uniaxial compression and three-point bending, was conducted to determine elastic and post-yield properties. Micro-computed tomography (μCT) was used to quantify structural parameters and assess tumor heterogeneity in unablated tumor specimens. Mechanical testing revealed significantly higher elastic and post-yield properties in normal bone compared with tumor-affected bone.ResultsNo significant differences were detected between ablated and unablated conditions within normal bone or within tumor-affected bone, indicating that histotripsy did not compromise the structural integrity of normal bone nor exacerbate damage in tumor-affected bone. Unablated trabecular tumor specimens exhibited higher and more variable elastic modulus and ultimate strength values than other groups, highlighting tumor heterogeneity. μCT analysis confirmed substantial structural heterogeneity among unablated tumor specimens, particularly in bone volume fraction.ConclusionHistotripsy preserves the mechanical integrity of both tumor-affected and normal bone. These results support histotripsy’s potential as a non-invasive, bone-sparing, patient-specific therapeutic approach for clinical osteosarcoma.